Estimating the Impact of External Shocks on the ECCU : Application to the COVID Shock - Parlak, Vivian; Salinas, Gonzalo; Vargas, Mauricio (Washington, D.C. : International Monetary Fund, 2021)
We measure the impact of frequent exogeneous shocks on small ECCU economies, including changes to global economic activity, tourism flows, oil prices, passport sales, FDI, and natural disasters. Using Canonical-Correlation Analysis (CCA) and dynamic panel regression analysis we find significant effects of most of these shocks on output, while only fluctuations in oil prices have significant effects on inflation. Results also suggest a significant impact of FDI and passport sales on the external balance, a link that CCA identifies as the strongest among all analyzed relations. The model also shows how Covid-19 related shocks lead to substantial contractions in output in all ECCU countries and deterioration of the current account balance in most of them, depending on countries' tourism dependency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Classification Methods; Cluster Analysis; Factor Models; Multiple or Simultaneous Equation Models; Principal Components